Implementing Various Strategies in Teaching English through Literature in Islamic Boarding School - Untung Pararean Adjie Saputra; Wirda Farfaza Nabila Rusafi Rusafi; Wahyu Indah Mala Rohmana (English Education Postgraduate Program, Universitas Negeri Manado, 2024)
The study Implementing Various Strategies in Teaching English through Literature in Islamic Boarding School explores the challenges of teaching English to Indonesian students particularly those in rural areas and the importance of finding successful techniques to improve their language proficiency The research focuses on the English literature classroom at Amanatul Ummah Islamic Boarding School in Pacet Mojokerto Indonesia and the strategies employed in teaching English through literature The qualitative research methodology used in the study involves in depth interviews with an English teacher at the school and the analysis of teaching strategies student engagement and motivation The results highlight the school s commitment to structured and systematic learning approaches including the use of the Wahdah technique for Quran memorization The study also discusses the school s unique approach to teaching English through literature which includes exposing students to a variety of literary texts using pre reading while reading and post reading activities and integrating literature classes with other subjects such as history social studies and Islamic studies The discussion analyzes the current teaching strategies their effectiveness and the potential of the new methods suggested comparing them with the strategies proposed by experts in the field of English language education The study aims to offer insightful information to educators and policymakers at Islamic boarding schools and to influence future research and policy development in the field of English language instruction< em>< p>